1994
DOI: 10.4141/cjas94-079
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of different layers of joint cartilage from pigs treated with and without recombinant porcine somatotropin (rpST)

Abstract: It has been reported that the ad'minisiration of rpsr induces the expeiiment was-reviewed and approved by the.Univera high incidenci and severity of osteochondrosis in growing sity of Alberta Animal Care Committee to ensure adherence and-finishing pigs (Evock et al. 1988), and results in reduced to Canadian Council of Animal Care guidelines. collagen undgti.oiurninoglycan concentrations in the weight-Fresh humeral condyles from both elbows were collected beari-ng u.eu-of .loint "u.iitug" (He et al. 1994

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This is in agreement with a study of the effect of recombinant pig growth hormone, which induces high levels of OC, on the glycosaminoglycan content of joint cartilage in pigs. Total PG content of articular cartilage was unchanged, but was reduced in the deeper layers of the epiphyseal cartilage [18]. There are a number of conflicting reports documenting either increased or decreased levels of general PGs, or individual PG components of the extracellular matrix in OC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with a study of the effect of recombinant pig growth hormone, which induces high levels of OC, on the glycosaminoglycan content of joint cartilage in pigs. Total PG content of articular cartilage was unchanged, but was reduced in the deeper layers of the epiphyseal cartilage [18]. There are a number of conflicting reports documenting either increased or decreased levels of general PGs, or individual PG components of the extracellular matrix in OC.…”
Section: Discussionmentioning
confidence: 92%
“…There are a number of conflicting reports documenting either increased or decreased levels of general PGs, or individual PG components of the extracellular matrix in OC. However, changes were restricted to the growth cartilage and were either unchanged due to the absence of lesions or not determined in the articular cartilage of the joints examined [5,17,18,33]. Nakano et al [31] concluded that biochemical changes in PGs only occur in severely affected joint cartilage, and not in cartilage with early OC/OA.…”
Section: Discussionmentioning
confidence: 99%